Use of heat foci in the evaluation of burned areas and of forest fires in Paragominas, Pará, Brazil - Sales, Gil Mendes; Pereira, Jorge Luis Gavina; Thalês, Marcelo Cordeiro; Poccard-Chapuis, René; Almeida, Arlete Silva de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
The number of occurrences of heat sources has increased in recent years in Brazil, showing a worrying perspective in the occupation dynamics. Proper use of these monitoring data can support effective and coherent local management policies to a new global environmental order. Therefore, the objective of this study was to evaluate the use of heat source data on the burning dimension in the municipality of Paragominas, State of Pará, in the 2015-2016 cycle, in order to subsidize the understanding of fire recurrence in the landscape to provide a constructive perspective of prevention and combat, whose objective cadence pressures, mainly on forest remnants and, consequently, environmental quality. For this purpose, data from INPE’s Burn Database, remote sensing products and geoprocessing and image interpretation techniques were used to understand such particularities occurring in the period. The results showed a low coincidence of heat focuses with a fire risk of over 50% on the mapped burned areas, around 20% in 2015 and 10% in 2016. On the other hand, they were important temporal indicators of the pressure zones to forest remnants; indicating, even, occurrence in many of the agricultural settlements.
Keywords: Fire; Heat spots; Territorial management; Paragominas